2013
DOI: 10.1186/1748-5908-8-134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a web-based intervention to reduce antibiotic prescribing for LRTI in six European countries: quantitative process analysis of the GRACE/INTRO randomised controlled trial

Abstract: BackgroundTo reduce the spread of antibiotic resistance, there is a pressing need for worldwide implementation of effective interventions to promote more prudent prescribing of antibiotics for acute LRTI. This study is a process analysis of the GRACE/INTRO trial of a multifactorial intervention that reduced antibiotic prescribing for acute LRTI in six European countries. The aim was to understand how the interventions were implemented and to examine effects of the interventions on general practitioners’ (GPs’)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…Intervention content was based on theories of behaviour change and particularly focused on increasing self-efficacy, one's belief that one can carry out a particular behaviour at a given time. 16,17 Clinicians reported being more confident in diagnosing an infection when using the CRP test and in explaining a nonprescribing decision to patients, and this appeared to be a result of training videos provided within interventions. Clinicians' expectations of the outcome of a consultation are also likely to have changed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intervention content was based on theories of behaviour change and particularly focused on increasing self-efficacy, one's belief that one can carry out a particular behaviour at a given time. 16,17 Clinicians reported being more confident in diagnosing an infection when using the CRP test and in explaining a nonprescribing decision to patients, and this appeared to be a result of training videos provided within interventions. Clinicians' expectations of the outcome of a consultation are also likely to have changed.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Lastly, the results supported the quantitative evaluation of GRACE INTRO, which indicated that clinicians perceived reducing prescribing as less risky following the intervention, and clinicians in the communication group reported increased confidence to reduce prescribing. 17 Previous qualitative work has also explored clinicians' views of communication skills training as a way to promote prudent prescribing. The STAR study evaluated a multifaceted educational intervention delivered through both online and outreach visit training, and was centred on communication skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Communication group patients had lesser belief in the necessity of antibiotics and greater belief in the harms of antibiotics. In contrast, patients in the CRP group had lower enablement scores.…”
mentioning
confidence: 97%
“…8 Physicians used CRP testing more selectively, for 38 % of patients. Beyond the reliability of implementation, physicians in the communication group gained confidence in their ability to reduce antibiotic prescribing, and physicians in the CRP group lost confidence.…”
mentioning
confidence: 99%